Rotational ‘cooling’ and ‘heating’ of OH(+)((3)Σ(−)) by collisions with He: quantum dynamics revealing propensity rules under ion trap conditions (†) - González-Sánchez, L. (Taylor & Francis, 2018)

(untitled) (Mol Phys)
Multichannel scattering calculations are presented for the low-energy collisions of the OH(+) cation and He atoms, using an ab initio evaluation of the interaction potential, which had been obtained in earlier work, and a time-independent, multichannel treatment of the quantum dynamics carried out in this study using our in-house scattering code ASPIN. Given the presence of spin-rotation coupling effects, within an essentially electrostatic formulation of the interaction forces with He atoms in the trap, the ensuing propensity rules which control the relative size of the state-changing cross sections and of the corresponding inelastic rates, also computed at the most likely temperatures in an ion trap, are presented and analysed in detail.